Analysis of PIXY Cosmetics Purchase Factors - Evi, Tiolina; Pramesworo, Ign. Septo (Institut Agama Islam (IAI) SEBI, 2023)
The purpose of this study was to analyze the effect of product quality, price and promotion on purchasing decisions of fairy cosmetics. The data used in this study were obtained from primary data using a questionnaire distributed to 100 respondents who use pixy cosmetics who live in Jakarta, which were determined using a purposive sampling technique. The analysis used in this study was multiple linear analysis, which was processed using the SPSS version 25 application. The results showed that product quality had a positive and significant effect on purchasing decisions, Price had a positive and significant effect on purchasing decisions, Motivation had a positive and significant effect on purchasing decisions . The promotion waas the most dominant influence compared to others.